A structured framework for net zero transition in manufacturing - Kaur, Rashmeet; Patsavellas, John; Salonitis, Konstantinos (Springer, 2025)
Despite increasing pressure to decarbonise, manufacturing organisations globally lack standardised frameworks to benchmark their overall progress toward net zero goals, relying instead on fragmented, process-oriented models. To address this gap, this paper introduces the Net Zero Maturity Model (NZMM), a structured framework designed to help manufacturing organisations evaluate their current maturity levels and select the most pertinent strategic actions toward net zero by avoiding prioritisation conundrums. The NZMM was developed through an extensive literature review that identified key thematic areas critical for net zero manufacturing, validated and ranked through input from 30 recognised industry practitioners. The resulting model integrates three maturity levels across seven key dimensions, addressing Scope 1, 2, and particularly the complexities in Scope 3 emissions. The framework serves as a practical decision-making tool to reduce uncertainty and facilitate structured decision-making, allowing organisations to gauge their net zero maturity and systematically navigate capability development. Validation with two manufacturing organisations demonstrated the NZMM's effectiveness in identifying capability gaps and prioritising improvement initiatives. The NZMM contributes to existing literature and industry practice by introducing a cohesive, standardised approach that bridges the gap between narrowly focused, process-specific models and holistic organisational assessment needs.
Keywords: 4014 Manufacturing Engineering; 40 Engineering; 35 Commerce, Management, Tourism and Services; 3507 Strategy, Management and Organisational Behaviour; Generic health relevance; 13 Climate Action; 9 Industry, Innovation and Infrastructure; sustainable manufacturing; manufacturing systems